Anafilaksi tablosu ile gelen rüptüre akciğer hidatik kist olgusu - (:unkn) unknown (My University, 2006)
Ekinokokkozis ya da hidatik hastalık ekinokok larvaları ile oluşur. Akciğer kist hidatik hastalığı genellikle asemptomatik seyreder, ancak bazen kist içeriğinin ekspektorasyonu veya komşu dokulara basısı sonucu semptomlar ortaya çıkabilir. Antihelmintik tedavi veya perkütan aspirasyon sonrası kist rüptürüne bağlı pnömotoraks ve allerjik reaksiyonlar görülebilmekle birlikte, spontan kist rüptürüne bağlı anafilaksi ile gelen akciğer kist hidatiği olgusu çok nadirdir. Burada ürtiker ve solunum sıkıntısı ile hastaneye başvuran ve rüptüre akciğer kist hidatiği tanısı alan 16 yaşında bir olgu sunarak, allerjik reaksiyonla başvuran hastalarda ayırıcı tanıda özellikle hastalığın endemik olduğu bölgelerde kist hidatik tanısına dikkat çekmek istenmiştir.

Echinococcosis or hydatid disease is caused by larvae of Echinococcus. Pulmonary hydatid cysts are usually asymptomatic but patients may occasionally develop symptoms due to expectoration of cyst contents or compression of the surrounding structures. Rupture may occur during antihelminthic therapy or percutaneous aspiration and can lead to severe complications such as pneumothorax and allergic reactions. Anaphylactic reactions due to spontaneous rupture of pulmonary hydatid cyst are rare. We report a 16 year old girl who admitted to hospital with urticaria and respiratory distress and diagnosed as ruptured pulmonary hydatid disease inorder to emphasize importance of hydatid disease in the differential diagnosis of anaphylaxis particularly when patients reside in endemic areas.
Ruptured pulmonary hydatid cyst presented as anaphylactic reaction: A case report
Keywords: Solunum Sistemi